From tellers to sellers : changing employment relations in banks - Regini, Marino, 1943-; Kitay, Jim; Baethge, Martin (MIT Press, 1999)
"This book is the outcome of intensive study of selected banks in Australia, France, Germany, Great Britain, Italy, the Netherlands, New Zealand, Spain, and the United States. As part of a larger project on industrial relations and human resource management practices, researchers in each country explored the changing industry context and competitive strategies in relation to a number of employment relations practices, such as skill formation and development, work organization, staffing arrangements, job security, compensation, and industrial relations. The introductory chapter provides an overview of the main research findings. The country chapters present detailed analyses of the findings, and the conclusion assesses the role of markets technology, and institutions in employment relations and discusses the interpretive frameworks that help make sense of their change and variation across countries."--Jacket